الالكستيميا (الأولية ، الثانوية) ، و علاقتهما بنموذج العوامل الخمسة الكبرى للشخصية - فاسي, آمال (جامعة الوادي - University of Eloued, 2022)
يصف مصطلح الالكستيميا او عجز التعبير الانفعالي نظاما خاصا متعلق بكيفية ادارة الحياة الانفعالية، و الذي يعرف من خلال عدم القدرة أوالصعوبة في وصف للعواطف والانفعالات أو عدم الدراية بالمشاعر الداخلية. مع صعوبة كبيرة في التمييز بين المحتويات العاطفية والاحاسيس الجسدية ، بالإضافة الى الحياة العملية الموجهة نحو الاستثمار الخارجي . تهدف دراستنا الى تبيين نوعين من الالكستيميا، فالنوع الاول يعرف كسمة في الشخصية ، أما النوع الثاني فيعتبر كنظام دفاعي اتجاه الوضعيات الحياتية، مخلفة بذلك إما نشاط عقلي خاص أو اضطرابات نفسية أو جسدية . بالإضافة الى تبين العلاقة ما بين الالكستيميا و الشخصية من خلال نموذج 5 عوامل (عامل الانبساط، عامل الانفتاح على الخبرات، عامل الطبع اللطيف، عامل الطبع الواعي، عامل الابعاد السلبية) . الكلمات المفتاحية: الألكستيميا، الالكستيميا الاولية ، الالكستيميا الثانوية ، نموذج 5 عوامل. The term " Alexithymia" or the impotence of emotional expression describes a special system related to how emotional life is managed. Which is known through inability or difficulty in describing emotions and emotions or lack of knowledge of internal feelings with great difficulty in distinguishing between emotional content and physical sensations in addition to working life geared towards foreign investment. Our study aims to identify two types of Alexithymia, the first type is known as a personality trait, while the second type is considered as a defense system towards life situations, leaving either special mental activity or psychological or physical disorders. In addition to showing the relationship between Alexithymia and personality through a model of 5 factors (diastolic factor, openness factor to experiences, gentle nature factor, conscious nature factor, negative dimensions factor).
Primary, secondary alexithymia and their relationship to the big five-factor model of personality
مقال
Keywords: الألكستيميا، الالكستيميا الاولية ، الالكستيميا الثانوية ، نموذج 5 عوامل.; Alextemia, primary alextemia, secondary alextemia, model of 5 factors